Pengaruh Pelatihan Resusitasi Jantung Paru Menggunakan Video Terhadap Sikap Kesiagaan Pertolongan Pertama Remaja Pada Pasien Henti Jantung - kusyani, Asri; ana, Karisma dwi (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
Adolescents need to know the main action to be given to OHCA (out-of-hospital cardiac arrest) patients because people who were close to cardiac arrest patients have an essential role in performing the resuscitation. The rapid resuscitation in the first few minutes will increase the chance of survival by double to triple. Increasing the ability of nonexpert people to perform resuscitation can be performed by providing training using standardized American Heart Association resuscitation videos. The study aimed to determine the change in resuscitation attitudes among adolescents after receiving the training video. The quasi-experimental design was used within a pretest-posttest group. The population of this study was 160 adolescents, and 94 respondents were recruited using a purposive sampling technique according to the inclusion criteria for high school youth who had never received cardiopulmonary resuscitation (CPR) training inside or outside of school. The variables in this study were training videos and attitudes to the practice. Data were analyzed using the Wilcoxon test. The results showed the attitudinal variable (p=0.0000.05). Among 94 respondents whole had a positive attitude (100%) before and after receiving the CPR training video. The attitudes are increasing after the implementation of the CPR training video compared to before the intervention. Providing first aid training to help cardiac arrest patients using training videos to the adolescent by healthcare team needs to be increased.